МЕТОДИ КОМПЕНСАЦІЇ СПОТВОРЕНЬ ОЦІНОК ФАЗИ У БАГАТОЗОНДОВИХ МІКРОХВИЛЬОВИХ ВИМІРЮВАЧАХ - DROBAKHIN, O. O.; OLEVSKYI, O. V. (текст 3, 2025)
DOI: https://doi.org/10.15407/itm2025.02.072 This paper addresses the problem of the accuracy of contactless relative displacement measurement with the help of a multiprobe measuring line in the microwave range. Attention is given to measurement errors that arise from inaccuracies in the probe placement and probe spacing measurement and inaccuracies in oscillator frequency setting. These inaccuracies can be caused by excessive vibrations and temperature variations. The paper overviews two standard methods: the discrete Fourier transform method and the two-probe method. New approaches based on Prony’s method and the normalized propagation constant correction method are studied. Prony’s method approach uses a modified version of Prony’s method in order to reduce the required number of probes. The novel approach is based on approximating the signal model with the help of a linear approximation of the harmonic component with a shifted value of the normalized propagation constant. The former method significantly reduces the signal distortion, while the latter is sufficient for small distortions and shows a faster computational speed. The methods were first tested on a deterministic noiseless model with phase distortions due to errors in the propagation constant followed by testing them on a model both with propagation constant errors and with additive white Gaussian noise present. The tests gave empirical ranges of applicability of each of the methods including the standard ones based on their performance. For the proposed methods, these ranges are sufficient for real-world applications, and they mainly impose restrictions on the probe spacing measurement accuracy because the oscillator frequency accuracy provided by modern equipment lies well within them. The methods improve the relative displacement measurement accuracy for a waveguide system model subject to vibrations that affect the electrical probe spacing. REFERENCES 1. Doronin A. V., Gorev N. B., Kodzhespirova I. F., Privalov E. N. A way to improve the accuracy of displacement measurement by a two-probe implementation of microwave interferometry. Progress in Electromagnetics Research M. 2013. V. 30. Pp. 105-116.https://doi.org/10.2528/PIERM13020504 2. Ghannouchi F. M., Mohammadi A. The Six-Port Technique with Microwave and Wireless Applications. Artech House, 2009. 236 рp. 3. Pylypenko O. V., Gorev N. B., Doronin A. V., Kodzhespirova I. F. Phase ambiguity resolution in relative displacement measurement by microwave interferometry. Teh. Meh. 2017. No. 2. Pp. 3-11 4. Drobakhin O. O. Development of measurement methods in microwave and terahertz ranges of electromagnetic waves in Ukraine (Review). Radioelectronics and Communications Systems. 2024. V. 67. No. 4. Pp. 161-179.https://doi.org/10.3103/S0735272724040034 5. Andreev M. V., Drobakhin O.O., Saltykov D. Yu. Techniques of measuring reflectance in free space in the microwave range. 2016 9th International Kharkiv Symposium on Physics and Engineering of Microwaves, Millimeter and Submillimeter Waves (MSMW 2016). June 20-24 2016. Pp. 1-4.https://doi.org/10.1109/MSMW.2016.7538213 6. Ghannouchi F. M., Bosisio R. G. A wideband millimeter wave six-port reflectometer using four diode detectors calibrated without a power ratio standard. IEEE Transactions on Instrumentation and Measurement. 1991. V. 40. No. 6. Pp. 1043-1046. https://doi.org/10.1109/19.119791 7. Doronin A. V., Gorev N. B., Kodzhespirova I. F., Privalov E. N. Displacement measurement using a two-probe implementation of microwave interferometry. Progress in Electromagnetics Research C. 2012. V. 32. Pp. 245-258.https://doi.org/10.2528/PIERC12071805 8. Pylypenko O. V., Gorev N. B., Doronin A. V., Kodzhespirova I. F. Experimental verification of a two-probe implementation of microwave interferometry for displacement measurement. Teh. Meh. 2017. No. 1. Pp. 5-12. 9. Andreev M. V., Drobakhin O. O., Saltykov D. Yu., Gorev N. B., Kodzhespirova I. F. Three-probe microwave interferometry for measuring displacement of mechanical objects with account for antenna reflectivity. Radioelectronics and Communications Systems. 2022. V. 65. No. 4. Pp. 177-185.https://doi.org/10.3103/S0735272722040021 10. Drobakhin O. O. Prony's-method identification of parameters of model which is sum of exponential functions. Optoelectronics, Instrumentation, and Data Processing. 1989. No. 4. Pp. 37-42. 11. Andreev M. V., Drobakhin O. O., Saltykov D. Yu. Complex reflection coefficient determination via digital spectral analysis of multiprobe reflectometer output signals. 2017 IEEE First Ukraine Conference on Electrical and Computer Engineering (UKRCON) Proceedings. 2017. Pp. 180-183.https://doi.org/10.1109/UKRCON.2017.8100468 12. Drobakhin O. O., Plaksin S. V., Riabchii V. D., Saltykov D. Yu. Microwave Enginering and Semiconductor Electronics. 3rd ed. Dnipro: Dnipro National University, 2018. 344 pp. (In Ukrainian). 13. Pozar D. M. Microwave Engineering. 4th ed. US: John Wiley & Sons, Inc., 2011. 752 pp.